Implementasi IoT Smart-Alarm System sebagai Peringatan Dini Jalan Curam RW 7 Tegalsari - Miftakhur Rahman; Tegar Luqman Hakim; Hilda Rahmah (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2026)
The steep road access in the Tegalsari area poses potential safety risks for road users, particularly under limited lighting conditions and low visibility. This situation not only increases vulnerability to traffic accidents but also affects the accessibility and mobility of the community, including Micro, Small, and Medium Enterprises (MSMEs) in conducting distribution activities and Cash on Delivery (COD) services. Addressing this issue requires an early warning system capable of providing automated, real-time information to enhance road users' safety and awareness. Based on these conditions, this community service activity aims to implement an IoT Smart-Alarm System as an Internet of Things (IoT)-based early warning system on steep road access to support MSME accessibility, specifically in RW 07, Tegalsari Village. The implementation method was carried out through several stages: site survey, community needs analysis, hardware and software system design, device installation, and direct field testing. The system was designed using an ESP32 microcontroller connected to an HC-SR04 ultrasonic sensor, a DFPlayer Mini, a speaker, and LED indicators. The sensor functions to detect the presence of vehicles passing through specific areas, which then triggers the system to automatically activate voice and light warnings to alert road users. Based on the implementation results, the system operates effectively in detecting vehicle objects. The application of this technology is expected to enhance road user safety, minimize accident risks on steep roads, and support the utilization of Internet of Things technology in developing smart technology-based communities.